Noise Performance Investigation of AlGaN/GaN HEMT With Tall Gate Stem for Millimeter-Wave LNA Application - Ping-Hsun Lee; Yueh-Chin Lin; Heng-Tung Hsu; Cheng-Hsien Yu; Yi-Fan Tsao; Pin Su; Edward Yi Chang (IEEE Journal of the Electron Devices Society, 2023)
In this research, $Γ $ -gated AlGaN/GaN HEMTs with different layout designs and heights of gate stems were fabricated to investigate their impacts on the noise performance in the Ka-band. First, devices with 4 types of gate peripheries were prepared to optimize the layout structure for best noise performance since the values of parasitic capacitance and resistance, which are detrimental to the noise characteristic, vary as the gate widths and the number of fingers change. The device with gate width of $4× 50\,\,μ { m}$ achieved the optimal noise performance, minimum noise figure (NFmin) of 1.5 dB and associated gain of 6.2 dB at 28 GHz. Next, devices with different gate stem heights were fabricated following the $4× 50\,\,μ { m}$ layout pattern. The raised gate structure was applied to reduce the parasitic capacitance of the device for RF power performance enhancement, but a taller gate stem unfortunately results in the increment of gate resistance. Therefore, the impact of stem height on NFmin remains unknown. According to the experiment results, the device with a stem height of 200 nm stands out to be a viable compromise for the noise and output power performance in the Ka-band, thus providing a positive outlook for the feasibilities of single-chip circuit integration of both LNA and PA at millimeter-wave spectrum.